Motivacija dijakov Srednje zdravstvene šole v Novem mestu za nadaljnje šolanje - Jezerinac, Mirna (Obzornik zdravstvene nege, 2000)
The article summarizes the findings of the research work on the motivation of high school students in Novo mesto for continuing education. Ninety four students from the High School of Nursing in Novo mesto, and their degree of interest and motivation for continuing education, were investigated. Interest and motivation for continuing education are high. In students, extrinsic motivational factors prevail. Most of the students want to continue with theireducation and achieve better social position. The results of the researchshow that certain objective goals prevail, while craving for knowledgeis not in the first place. The results reveal low intrinsic motivation for further study. Inner motivation is usually stronger and more durable; however intrinsic and extrinsic motivation influence each other.
Keywords: Adolescence; dijaki; education; Education, nursing; Faculty, nursing; izobraževanje; motivacija; Motivation; nega bolnika; Nursing care; Questionnaires; srednje zdravstvene šole